2019
DOI: 10.4143/crt.2018.249
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram, a Re-positioned Aldehyde Dehydrogenase Inhibitor, Enhances Radiosensitivity of Human Glioblastoma Cells In Vitro

Abstract: Radiosensitivity of glioblastoma cells were preferentially enhanced by pre-irradiation DSF treatment compared to normal cell, especially radioresistant cells such as MGMT-wt cells. Induction of apoptosis or inhibition of DNA damage repair may underlie DSF-induced radiosensitization. Clinical benefit of combining DSF with radiotherapy should be investigated in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
1
21
2
Order By: Relevance
“…Likewise, our present study did not identify any radiosensitization of both glioblastoma stem-cell cultures by disulfiram/Cu 2+ . This is in seeming contrast to previous studies that show a disulfiram/Cu 2+ -mediated radiosensitization in patient-derived spheroid glioblastoma stem (brain-tumor-initiating) cells [12] and human glioblastoma cell lines [58]. Notably, in the latter study, only one (U138MG) and in tendency also a second (T98G) out of five glioblastoma lines were radiosensitized by disulfiram (75-100 nM) when grown in Cu 2+ -containing serum-supplemented medium and when using clonogenic survival as the endpoint [58].…”
Section: Disulfiram As a Radiosensitizercontrasting
confidence: 97%
“…Likewise, our present study did not identify any radiosensitization of both glioblastoma stem-cell cultures by disulfiram/Cu 2+ . This is in seeming contrast to previous studies that show a disulfiram/Cu 2+ -mediated radiosensitization in patient-derived spheroid glioblastoma stem (brain-tumor-initiating) cells [12] and human glioblastoma cell lines [58]. Notably, in the latter study, only one (U138MG) and in tendency also a second (T98G) out of five glioblastoma lines were radiosensitized by disulfiram (75-100 nM) when grown in Cu 2+ -containing serum-supplemented medium and when using clonogenic survival as the endpoint [58].…”
Section: Disulfiram As a Radiosensitizercontrasting
confidence: 97%
“…As expected, it was reported that the percentage of γH2AX-positive cells after irradiation decreased rapidly in T98G cells. In contrast, the proportion of γH2AX-positive cells after irradiation sustained until 24 h in U373 [ 33 ]. For this reason, while U373 cell was regarded as temozolomide-sensitive cell, T98G cell was known to be relatively resistant to temozolomide [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since GBM is considered as a radioresistant tumor [3] and most of the recurrence occurs in the radiotherapy field [4], radiosensitization of the tumor is an important target to improve the outcome in patients with GBM. Therefore, multiple radiosensitizing strategies are actively under development, including PI3K pathway inhibitors [5], DNA repair inhibitors [6], hyperthermia [7], aldehyde dehydrogenase inhibitors [8], and high atomic number (high-Z) metal nanoparticles (NPs) [9].…”
Section: Introductionmentioning
confidence: 99%